The interplay of wind and uplift facilitates over-water flight in facultative soaring birds. Issue 1958 (8th September 2021) - Nourani, Elham; Bohrer, Gil; Becciu, Paolo; Bierregaard, Richard O.; Duriez, Olivier; Figuerola, Jordi; Gangoso, Laura; Giokas, Sinos; Higuchi, Hiroyoshi; Kassara, Christina; Kulikova, Olga; Lecomte, Nicolas; et al.
Abstract : Flying over the open sea is energetically costly for terrestrial birds. Despite this, over-water journeys of many birds, sometimes hundreds of kilometres long, are uncovered by bio-logging technology. To understand how these birds afford their flights over the open sea, we investigated the role of atmospheric conditions, specifically wind and uplift, in subsidizing over-water flight at a global scale. We first established that Δ T, the temperature difference between sea surface and air, is a meaningful proxy for uplift over water. Using this proxy, we showed that the spatio-temporal patterns of sea-crossing in terrestrial migratory birds are associated with favourable uplift conditions. We then analysed route selection over the open sea for five facultative soaring species, representative of all major migratory flyways. The birds maximized wind support when selecting their sea-crossing routes and selected greater uplift when suitable wind support was available. They also preferred routes with low long-term uncertainty in wind conditions. Our findings suggest that, in addition to wind, uplift may play a key role in the energy seascape for bird migration that in turn determines strategies and associated costs for birds crossing ecological barriers such as the open sea.